Sinergi Mahasiswa KKM dan Warga dalam Program Penghijauan Lahan Milik Kelompok Wanita Tani di Kelurahan Pageragung - Popi Dayurni; Basrowi Basrowi; Galuh Mulyawan; Virnanda Arini Firman; Nepi Andriani; Faqurah Nurliyana (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service program aims to increase awareness and involvement of residents in land reforestation efforts as part of environmental conservation efforts. This activity focuses on planting crops owned by the Women Farmers Group in Pageragung Village. Through participatory methods, KWT members together with students explore the land, select appropriate types of seeds, and plant and maintain plants. In addition to ecological benefits, the harvest of vegetables provides additional sources of income for the local community. This activity also succeeded in raising awareness of the importance of environmental conservation among the community. The findings of this program highlight the effectiveness of a community-based approach in implementing land reforestation and provide a basis for similar initiatives in the future.